Personality Berpengaruh terhadap Terjadinya Stress Kerja Perawat di Ruang Rawat Inap Rumah Sakit Umum Kota Salatiga - Sasanti, Serafina Damar; Shaluhiyah, Zahroh (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2016)
ABSTRACTApproximately 50.9 % of nurses working in four provinces in Indonesia in 2006 suffered Work Stress. Nurses often experience dizziness and fatigue, due to a high workload. This causes increased absenteeism, decreased productivity so that the impact on the quality of hospital services. The purpose of this study was to determine the effect of work stress Personality of the nurse in the inpatient unit District General Hospital Municipality Salatiga. This type of research is expalanatory research with cross sectional study involving 149 inpatient nurses. The result showed nurses who experience job stress is a nurse who has a personality type A which is expected to policy holders in the system toughest of recruits pay attention to the type of personality to be placed in the appropriate places.Keywords: personality, job stress of nurses